2021
DOI: 10.1111/dmcn.14993
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood neurodevelopmental outcome after open prenatal spina bifida aperta repair

Abstract: Aim To investigate neurodevelopmental outcome of children with open prenatal spina bifida aperta (SBA) repair. Method Prenatal SBA repair was performed in 130 fetuses at the Zurich Center between 2010 and 2019. Seventy‐seven children underwent 1 year assessment with the Griffiths Mental Developmental Scales (Griffiths) and 65 with the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III) at 2 years. Anatomical and functional level and ambulation status were assessed. Descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We have already published data on early neurodevelopment of our cohort following fetal OSB repair, which showed a favorable outcome in the low-average range at 1 and 2 years of age 34 . Age-appropriate fine motor function was observed, with an expected delay in gross motor function 34 . In this study, we showed that UA-AREDF did not negatively influence the 2-year neurodevelopmental outcome of the children.…”
Section: Two-year Neurodevelopmental Outcomementioning
confidence: 86%
“…We have already published data on early neurodevelopment of our cohort following fetal OSB repair, which showed a favorable outcome in the low-average range at 1 and 2 years of age 34 . Age-appropriate fine motor function was observed, with an expected delay in gross motor function 34 . In this study, we showed that UA-AREDF did not negatively influence the 2-year neurodevelopmental outcome of the children.…”
Section: Two-year Neurodevelopmental Outcomementioning
confidence: 86%
“…In contrast, motor skills were improved in children with open prenatal change in spina bifida (SBA) repair. 7,8 As a consequence, a selection of the fetuses that may benefit of intrauterine surgery is necessary. In this attempt Hérbene José et al 1 despite failed to evidence significant differences in the TVOL between normal and spina bifida fetuses evidenced that in fetuses with spina bifida with presence of lower limb movement higher TVOL values were found compared to fetuses without lower limb movements.…”
Section: Commentarymentioning
confidence: 99%
“…Despite benefits and risks are still uncertain, long‐term data from the Management of Myelomeningocele Study cohort, published in showed no improvement in cognitive functioning in the prenatal repair group at primary school age compared to the postnatal group. In contrast, motor skills were improved in children with open prenatal change in spina bifida (SBA) repair 7,8 . As a consequence, a selection of the fetuses that may benefit of intrauterine surgery is necessary.…”
Section: Commentarymentioning
confidence: 99%
“…As such, they have scientifically validated, to an acceptable degree, the generalizability of the MOMS findings. Both these retrospective cohort studies suggest that single‐site fetal centers functioning outside of a randomized trial environment, respectively in Europe 3 and in the USA where results from independent centers were aggregated in the National Spina Bifida Patient Registry, 4 can achieve comparable short‐ and medium‐term outcomes to the MOMS trial.…”
mentioning
confidence: 97%
“…and Worley et al. have bridged this gap in knowledge by demonstrating different aspects of the effectiveness of fetal SBA surgery 3,4 . As such, they have scientifically validated, to an acceptable degree, the generalizability of the MOMS findings.…”
mentioning
confidence: 99%